Beyond cell proliferation in avian facial morphogenesis. Issue 3 (4th January 2016) - Linde‐Medina, Marta; Hallgrímsson, Benedikt; Marcucio, Ralph
Abstract : The upper jaw in vertebrates forms from several prominences that arise around the stomodeum or primitive mouth. These prominences undergo coordinated growth and morphogenesis to fuse and form the face. Undirected, regionalized cell proliferation is thought to be the driving force behind the morphogenesis of the facial prominences. However, recent findings suggest that directed cell behaviors in the mesenchyme (e.g., directed cell division, directed cell movement, convergent extension) might be required for successful face formation. Here we discuss the evidence for this view and how directed behaviors may interact with the basement membrane to regulate morphogenesis of the facial region. We believe that future research in these largely unexplored areas could significantly impact our understanding of facial morphogenesis. Developmental Dynamics 245:190–196, 2016 . © 2015 Wiley Periodicals, Inc. Key Findings: We outline a new morphogenetic model of early primary palate.